Microencapsulação de óleo de palma por coacervação complexa em matrizes de gelatina/goma arábica e gelatina/alginato - Marfil, Paulo Henrique Mariano [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Microencapsulation of palm oil may be able to protect it and promote its controlled release. For optimization of the microencapsulation process, it is necessary to quantify accurately the palm oil present externally and internally to the microcapsules. A spectrophometric method was developed and validated to be used in the determination of the efficiency of microencapsulation process of palm oil. First, the extraction of extern palm oil through five successive washes with organic solvent was standardized. Next, the best method to accomplish the rupture of the microcapsules was investigated. Through successive extractions with hexane, it was possible to determine the amount of palm oil contained internally. Measurements were made in a spectrophotometer and the proposed method was shown to be low cost, fast and of easy implementation. In addition, the validation step allowed us to observe that the method is safe and reliable, since it proved to be specific, accurate, precise and robust. Formation of electrostatic complexes between gelatin and sodium alginate was investigated as a possible system to microencapsulate palm oil by complex coacervation. Gelatin and sodium alginate solutions were prepared (0.25% w/v) in different pH values (2.0, 3.0, 3.5, 4.0, and 5.0) to zeta potential measurements. Turbidity (absorbance measurement at 590 nm) and morphology (light microscopy imaging) analyzes were carried out in blends of different gelatin:sodium alginate mixing ratios (0:1, 1:1, 2:1, 3:1, 4:1, 5:1, and 1:0) keeping a fixed amount of total polymers (0.25% w/v). Gelatin:sodium alginate blends at biopolymer ratios 1:1, 2:1, 3:1, and 4:1 were also prepared with 2.5% (w/v) total polymers to rheological analysis. Homogenization of palm oil (2.5% w/v) in gelatin solution was performed at 15,000 rpm for 5 minutes and the coacervation pH was 3.5 ± 0.1. The obtained coacervates were decanted for 24 hours, frozen (-40oC) and freeze-dried. The particle ...

A microencapsulação do óleo de palma pode ser capaz de protegê-lo e promover a sua liberação controlada. Para otimização do processo de microencapsulação é preciso quantificar de forma adequada o óleo de palma presente externamente e internamente às microcápsulas. Assim, realizou-se o desenvolvimento e validação de um método espectrofotométrico para ser utilizado na determinação da eficiência do processo de microencapsulação. Primeiramente padronizou-se o processo de extração do óleo de palma presente externamente através de cinco lavagens sucessivas com solvente orgânico. Posteriormente investigou-se a melhor forma de realizar o rompimento das microcápsulas. Através de extrações sucessivas com hexano foi possível determinar o óleo de palma contido internamente. As medidas foram feitas em espectrofotômetro e o método proposto mostrou-se de baixo custo, rápido e de fácil execução. Além disso, a etapa de validação permitiu observar que o método é seguro e confiável, uma vez que mostrou-se seletivo, exato, preciso e robusto. Foi investigada a formação de complexos eletrostáticos entre gelatina e alginato de sódio como um possível sistema para microencapsular óleo de palma por coacervação complexa. Preparou-se soluções de gelatina e alginato de sódio (0,25% m/v) em diferentes valores de pH (2,0; 3,0; 3,5; 4,0 e 5,0) para medidas de potencial zeta. Misturas desses dois biopolímeros em diferentes proporções de gelatina:alginato de sódio (0:1, 1:1, 2:1, 3:1, 4:1, 5:1, e 1:0) foram preparadas para ensaios de turbidimetria (medidas de absorbância em 590 nm) e análise morfológica (microscopia ótica). Na concentração de biopolímeros totais de 2,5% (m/v) foram preparadas misturas de gelatina:alginato de sódio (1:1, 2:1, 3:1 e 4:1) para análise reológica dos complexos formados. Óleo de palma (2,5% p/v) foi homogeneizado em solução de gelatina a 15000 rpm por 5 minutos, misturado à ...
Keywords: Tecnologia de alimentos; Microencapsulação; Dende; Coacervação complexa; Biopolimeros; Gelatina; Alginato de sódio; Microencapsulation